Anthropometry, strength, endurance and flexibility characteristics of elite male ice climbers and its comparison with non climbing - Vujic, S.; Manovski, K.; Kupper, T.; Mirkov, D.; Totic, S. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
Introduction: Purpose of this study was to compare elite male ice climbers and non climbers, their anthropometry, muscular strength, endurance and flexibility. The second aim was to extract variables which are specific for ice climbing and realize how they affect the competitive placement. Methods: Participants were divided in two groups. First group consisted of 23 male ice climbers who competed at the Ice Climbing World Cup 2010 organized by UIAA in Saas Fee (Switzerland) and they all passed to the final round. The other group consisted of 23 athletes of same age but from different non climbing sports, such as: rowing, fitness, handball, hockey, basketball, water polo, karate and cycling. Measurements included anthropometry, three different tests for flexibility, two for strength and two endurance tests. Results: Ice climbers has less height, mass, BMI, BMR and fat% in their body, comparing to non climbers. Ice climbers have significant less result for handgrip strength test in both hands, as well as SME, comparing to non climbers. Considering tests hip abduction and handgrip endurance, ice climbers shows significant better results. Conclusion: Results indicate that ice climbers have smaller height, weight, BMI, body fat% and handgrip strength for both hands comparing to non climbing athletes. On the other side, ice climbers need to know that except for need to developing endurance, strength and flexibility as main preconditions; success at competitions greatly depends on one`s experience which, as well as an improvement of climbing techniques, comes with age.